Liver fibrosis in patients with metabolic associated fatty liver disease is a risk factor for adverse outcomes in COVID-19 - Campos-Murguía, Alejandro; Román-Calleja, Berenice Monserrat; Toledo-Coronado, Israel Vicente; González-Regueiro, José Alberto; Solís-Ortega, Alberto Adrián; Kúsulas-Delint, Deyanira; Cruz-Contreras, Mariana; Cruz-Yedra, Nabila; Cubero, Francisco Javier; Nevzorova, Yulia Alexandrowna; Martínez-Cabrera, Carlos Fernando; Moreno-Guillén, Paulina; et al. (Digestive and liver disease, 2021)
Metabolic diseases are risk factors for severe Coronavirus disease (COVID-19), which have a close relationship with metabolic dysfunction-associated fatty liver disease (MAFLD). To evaluate the presence of MAFLD and fibrosis in patients with COVID-19 and its association with prognosis. Retrospective cohort study. In hospitalized patients with COVID-19, the presence of liver steatosis was determined by computed tomography scan (CT). Liver fibrosis was assessed using the NAFLD fibrosis score (NFS score), and when altered, the AST to platelet ratio index (APRI) score. Mann-Whitney U, Student´s t-test, logistic regression analysis, Kaplan-Meier curves and Cox regression analysis were used. 432 patients were analyzed, finding steatosis in 40.6%. No differences in pulmonary involvement on CT scan, treatment, or number of days between the onset of symptoms and hospital admission were found between patients with and without MAFLD. The presence of liver fibrosis was associated with higher severity scores, higher levels of inflammatory markers, requirement of mechanical ventilation, incidence of acute kidney injury (AKI), and higher mortality than patients without fibrosis. The presence of fibrosis rather than the presence of MAFLD is associated with increased risk for mechanical ventilation, development of AKI, and higher mortality in COVID-19 patients.